Slow and fast surface electromagnetic waves in planar structures contained left-handed material - Galaydych, V.K.; Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2015)
It was studied the properties of electromagnetic surface waves in left-handed material slab bounded by two semi-infinite nonmagnetic media with frequency dependent positive permittivity. It was assumed that all these media are isotropic and non-dissipative. It was shown that the phase velocities of waves are greater than the speed of light, and the group velocities are zero or negative.